DATA⁃DRIVEN RELIABILITY ANALYSIS MODEL OF QINGHAI⁃TIBET RAILWAY IN PERMAFROST ZONE - WANG JinBo; TANG JiaYin; LIU XinLing; WU Yi (Jixie qiangdu)
To ensure the safety of train operation in the plateau permafrost region of the Golmud⁃Lhasa section of the Qinghai Tibet Railway Phase II project,based on the original time series elevation data of railway subgrade in permafrost region,the product season model under various subgrade types is established to fit the uneven settlement degradation trajectory of subgrade and effectively predicted elevation values with confidence intervals.The differential operation was used to analyze the subgrade settlement degradation values.The failure time extrapolation method was used to complete the reliability evaluation,and the settlement threshold was set based on driving safety.The simulation results show that it can accurately forecast permafrost thawing degradation,and the research findings can be used by the logistics support department to conduct daily subgrade maintenance.